South Asia Network on Plant Genetic Resources (SANPGR): Proceedings of Fourth Meeting, Kathmandu, Nepal, 1-3 September 1998 - Mal, B.; Mathur, P.N.; Ramanatha Rao, V. (1999)
Regional plant genetic resources (PGR) networks can be very effective mechanisms for strengthening National Programmes, promoting exchange of germplasm, helping to set common agenda and priorities on conservation and use of PGR, formulating consistent policies, and in conveying regional views. Moreover, strengthening of regional networks is a priority activity, agreed to in the Global Plan of Action (GPA) for the conservation and use of Plant Genetic Resources for Food and Agriculture (PGRFA). For IPGRI, supporting such networks is an important part of our work in the Asia, Pacific and the Oceania region. In South Asia, such regional collaboration takes place through the South Asia Network on Plant Genetic Resources (SANPGR). This network brings together the national PGR coordinators nominated by member countries, namely, Bangladesh, Bhutan, India, Maldives, Nepal and Sri Lanka with the purpose of sharing information, needs and opportunities regarding PGR in the region. IPGRI office for South Asia, located in New Delhi, provides a Secretariat for this network. SANPGR meetings are held every 2 years hosted by one of the member countries. This reporting on the Proceedings of Fourth Network Meeting, which was held in Kathmandu, Nepal from 1-3 September 1998. Previous meetings were held in New Delhi, India in 1990, Peradeniya, Sri Lanka in 1992 and Dhaka, Bangladesh in 1995. The objectives of the Nepal SANPGR meeting were to take stock of activities carried out under the Convention on Biological Diversity and Global Plan of Action; to understand recent policy changes taking place at national and global levels, and to formulate action plans for regional collaboration. Finally, this meeting was to establish better linkages for PGR activities among the member countries.